Innovation and new capabilities: The search for new hr strategy - Tane Murgoski; Snezhana Hristova (University American College Skopje, 2022)
The purpose of this paper is to examine the impact of strategic HRM in Alkaloid Skopje, one of the biggest Macedonian pharmaceutical companies. Through the case study method, we provide empirical evidence by addressing Alkaloid Skopje's effort and the innovative strategy of its HR department, with a focus on improving the company's strategic competitiveness and overall performance. Structured interviews were conducted with employees from the HR department of Alkaloid Skopje who had long work experience in HR. The key objective of this case study is to explore current practices and strategic actions that potentially increase the performance of Alkaloid Skopje and could be further enhanced and implemented by top management in order to improve the competitive advantage of the company. Key findings of the case study show that strategic human resource management is an important factor in explaining company performance and competitive advantage. The practical implications acknowledge that to be competitive businesses must adopt new and innovative approaches in their strategic HR policies and practices that could be implemented with the aim of achieving better results for the organization.
Keywords: 330; HR department; HR strategy; competitive advantage; increasing performance; employee